Antioxidant, Anti-Inflammatory, and Multidrug Resistance Modulation Activity of Silychristin Derivatives - Jitka Viktorová; Simona Dobiasová; Kateřina Řehořová; David Biedermann; Kristýna Káňová; Karolína Šeborová; Radka Václavíková; Kateřina Valentová; Tomáš Ruml; Vladimír Křen; Tomáš Macek (MDPI AG, 2019)
Silychristin A is the second most abundant compound of silymarin. Silymarin complex was previously described as an antioxidant with multidrug resistance modulation activity. Here, the results of a classical biochemical antioxidant assay (ORAC) were compared with a cellular assay evaluating the antioxidant capacity of pure silychristin A and its derivatives (anhydrosilychristin, isosilychristin and 2,3-dehydrosilychristin A). All the tested compounds acted as antioxidants within the cells, but 2,3-dehydro- and anhydro derivatives were almost twice as potent as the other tested compounds. Similar results were obtained in LPS-stimulated macrophages, where 2,3-dehydro- and anhydrosilychristin inhibited NO production nearly twice as efficiently as silychristin A. The inhibition of P-glycoprotein (P-gp) was determined in vitro, and the respective sensitization of doxorubicin-resistant ovarian carcinoma overproducing P-gp was detected. Despite the fact that the inhibition of P-gp was demonstrated in a concentration-dependent manner for each tested compound, the sensitization of the resistant cell line was observed predominantly for silychristin A and 2,3-dehydrosilychristin A. However, anhydrosilychristin and isosilychristin affected the expression of both the P-gp (ABCB1) and ABCG2 genes. This is the first report showing that silychristin A and its 2,3-dehydro-derivative modulate multidrug resistance by the direct inhibition of P-gp, in contrast to anhydrosilychristin and isosilychristin modulating multidrug resistance by downregulating the expression of the dominant transmembrane efflux pumps.